Microbial Spectrum and Antiobiotic Sensitivity Patterns in Neonatal Blood Cultures: A NICU Based Study from Quetta, Pakistan - Ahmed, Syed Moeed; Shoaib, Muhammad; Ahmed, Waqas; Yasmeen, Samrina; Hina Muhammad Ali; Najeebullah (Pakistan Armed Forces Medical Journal, 2026)
Objective: To document the microbial spectrum and antibiotic sensitivity patterns in blood cultures of suspected neonatal sepsis. Study Design: Cross-sectional study. Place and duration: Neonatal Intensive Care Unit (NICU) of Combined Military Hospital, Quetta, Pakistan from May 2023 to Oct 2023. Methodology: The study analzyed neonates diagnosed with sepsis based on specific risk factors and clinical signs of bacterial infections. A thorough clinical assessment was conducted to confirm the presence of suspected sepsis. Specimens of neonates were processed using standard microbiological techniques for culture and sensitivity analysis. Results: In a total of 119 neonates, 68(57.1%) were boys. The median age was 2.00 days (1.00-4.00). Culture proven sepsis was found in 33(27.7%) specimens. Among 33 neonates with culture proven sepsis, Serratia marcescens, Acinetobacter baumannii, and Klebsiella pneumoniae were found to be the most frequent isolates, noted in 16(48.5%), 4(12.1%) and 4(12.1%) cases, respectively. Serratia marcescens were found to be highly resistant (100.0%) to ampicillin, cefipime, cefotaxime, and doxycyclin whereas these were 100.0% senstivie to Tazocin. Acinebobacter baumanni were found resistant 3rd generation cephalosporins but found 100.0% sensitive to Polymyxin B. Klebsiella pneumoniae were 100% sensitive to Polymyxin B. Enrerococcus species were 100.0% sensitive to Linezolid. Conclusion: Gender, birth weight, gestational age, and mode of delivery had significant association with culture-proven neonatal sepsis. The identification of Serratia marcescens, Acinetobacter baumannii, and Klebsiella pneumoniae as most commonly found isolates and high resistance patterns to most commonly antibiotics highlight the imperative for precise antibiotic selection guided by local resistance profiles.